Practice on creating a common reference concrete for Round Robin Testing programmes based on the experience from COST Action TU1404 - Serdar, Marijana (2020)
Round Robin Testing (RRT) is a well-known method for assessing the reproducibility of a test or verification of a new test procedure of almost any kind. In the EU funded network COST Action TU1404 ‘‘Towards the next generation of standards for service life of cement-based materials and structures”, an Extended Round Robin Testing program (RRT+ ) was planned as a fundamental tool to obtain input data for a range of concrete properties and validate non-standardised testing techniques. In this paper, detailed information on the planning, conduction and analysis of Phase 1 of the RRT+ is presented. The aim of Phase 1 was to define and confirm the best practice for creating a comparable reference concrete mix for RRT programmes. With a total of 45 laboratories from Europe, Japan and Canada, RRT+ was one of the most extensive round robin testing programmes targeting cement-based materials.